Health-risk behavior differences between boarding and non-resident students: Brazilian adolescent National School Health Survey - Matias Noll; Priscilla Rayanne e Silva Noll; Carlos Leandro Tiggemann; Daniela Costa Custodio; Erika Aparecida Silveira (BMC, 2020)
Abstract Background Studies that evaluated health-risk behaviors with boarding students are scarce. There are no studies with representative samples among adolescents residing in educational institutions in Latin America. To better assess the role of resident status on such behaviors, this study aimed to compare health-risk behaviors between boarding and non-resident students assessed by the Brazilian National Adolescent School Health Survey (PeNSE). Methods A cross-sectional study was conducted using the 2015 PeNSE database. A sample of 101,788 students (aged 11-19 years) from both public and private schools throughout all the Brazilian states completed the survey. A self-administered questionnaire was used to evaluate multiple health-related behaviors (sociodemographic characteristics; sexual behavior; cigarette use; drug use; and alcohol use). Poisson regression model-based analyses were performed and the effects measured through the prevalence ratio (PR) and its 95% confidence interval (CI). Results Boarding residents reported more health-risk behaviors than non-residents: previous sexual intercourse (PR 1.17, 1.10-1.25), smoking experience (PR 1.12, 1.03-1.21), monthly smoking frequency (PR 1.68, 1.42-1.99), monthly alcohol intake (PR 2.12, 1.79-2.50), inebriation (PR 1.51, 1.35-1.71), drug use experience (PR 1.23, 1.10-1.38), and monthly drug use frequency (PR 1.59, 1.31-1.94). Conclusions Boarding residents reported more health-risk behaviors than did non-residents. The results provide insights into an under-researched subject, helping to highlight potential points of intervention for supporting public health programs within the boarding-school student population.